2022
DOI: 10.1002/adfm.202201335
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Self‐Adhesive, Conductive Organohydrogels with Fast Gelation from Lignin‐Based Self‐Catalytic System for Extreme Environment‐Resistant Triboelectric Nanogenerators

Abstract: Conductive hydrogels have shown great promise in the field of sustainable power sources due to their unique features of sufficient flexibility, durability, and functional diversification. However, time-and energy-consuming polymerization process and poor adaptability in extreme environments severely impede their practical application in such an emerging field. Herein, a facile and universal self-catalytic system (AL-Cu 2+ ) based on alkali lignin (AL) macromolecule has been designed to rapidly fabricate conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 43 publications
2
106
0
Order By: Relevance
“…Compared with the previously reported conductive gels or polymeric films used to fabricate the TENG (Figure S19, Supporting Information), [ 12,39,57–60 ] this cellulose‐derived PDES‐based ionic conductive elastomer integrating with the excellent mechanical property, anti‐freezing, solvent‐resistance, and recyclability showed higher potential and value in the practical applications of the TENG and wearable self‐powered sensor.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared with the previously reported conductive gels or polymeric films used to fabricate the TENG (Figure S19, Supporting Information), [ 12,39,57–60 ] this cellulose‐derived PDES‐based ionic conductive elastomer integrating with the excellent mechanical property, anti‐freezing, solvent‐resistance, and recyclability showed higher potential and value in the practical applications of the TENG and wearable self‐powered sensor.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, with the increasing demands of the academic and society for sustainability and environmental friendliness, a variety of biomass resources such as cellulose, lignin, chitosan, etc., are emerging as powerful alternatives to fabricate the electrode materials. [ 10–13 ] Among these renewable biomass resources, cellulose as well as its derivatives, were frequently employed to fabricate electrode materials with the forms of membranes, aerogel, and hydrogel by the utilization of their intrinsic linear rigid hierarchical structures. [ 14–17 ] These studies demonstrated that the characteristics of cellulose including rigidity, abundant active hydroxy groups, porous and rough structure, and large surface area contributed to forming new types of electrode materials with adjustable mechanical and surface properties, which could further improve the durability and electrical output performance of TENG.…”
Section: Introductionmentioning
confidence: 99%
“…Even in an ambient environment, evaporation inevitably loses free water molecules from the system. Therefore, the practical use of artificial bionic skin in the field of HMI is still limited by its poor environmental stability. Using high-boiling-point solvents, including antifreeze or ionic liquids, for solvent replacement can effectively overcome the shortcomings of environmental instability. For example, Xu et al reported an antifreezing and flexible HMI device that works perfectly at −30 °C by replacing the original pure water solvent with ethylene glycol/water binary solvent . Although solvent replacement is used to solve the limitation of poor environmental stability of artificial bionic skin, the artificial bionic skin needs to rely on external energy to self-healing after injury, and the repair time is long and cannot 100% recover to the original state .…”
Section: Introductionmentioning
confidence: 99%
“…developed a hydrophobic and stable graphene-modified organohydrogel with antifreezing and antidrying abilities via soaking in a propylene glycol solution, which could possess a temperature tolerance as low as −60 °C and a significantly high gauge factor of 140 . Shao and co-workers reported a self-catalytic system of an alkali lignin-copper ion (AL-Cu 2+ ) for the rapid production of multifunctional organohydrogels in an alkaline water/ethylene glycol binary solvent, and meanwhile, the obtained organohydrogels could be used as extreme environmentally-resistant triboelectric nanogenerators . To date, despite some advanced antifreezing and antidrying organohydrogels having been reported based on this strategy and utilized in flexible electronic devices, it is still an enormous challenge to integrate excellent mechanical properties, high transparency, robust adhesiveness, wide temperature tolerance, and prominent solvent-resistant capabilities into a single gel polymer.…”
Section: Introductionmentioning
confidence: 99%